(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
We display a comparative study of different approaches that can be used to count the number of distinct elements in a stream data. The normal approach resembles the flajolet martin algorithm, the average approach, the median approach and the combined approach take into account more than one hash function. The paper provides a detailed analysis on a video stream with all the algorithms applied